A Simple Quaternization Method of Hyperbranched Polyamidoamine Polymer and Antimicrobial Activity Evaluation of Cationic Hyperbranched Polyamidoamine Polymer - Yingnakhon, W.; Srikulkit, K. (Asian Journal of Chemistry, 2013)
A series of cationic hyperbranched polyamidoamine (cationic PAMAM) containing terminal methyl ester end group (G-0.5, G0.5, G1.5, G2.5 and G3.5) were prepared by repetitive reactions between Michael addition and amidation to obtain the methyl ester group terminated hyperbranched PAMAM and then followed by a simple methylation of thus obtained PAMAM with dimethyl sulphate to obtain a series of cationic PAMAM. Characterizations by FTIR and 1H NMR analysis were performed to investigate the chemical structure. Thus obtained cationic PAMAM was padded into cotton fabric and followed by batching (24 h) and washing to remove all impurities. Following that the antibacterial activity of cationic PAMAM against S. aureus was evaluated by a quantitative test method according to AATCC test method 100 (antibacterial Finishes on textile material). As expected, the antimicrobial activity of cationic PAMAM increased with an increase in the molecular weight of PAMAM namely in the following order G-0.5-G0.5 < G1.5 < G2.5 < G3.5, respectively due to the increase in the cationic moieties in cationic PAMAM.